Perancangan Aplikasi Notifikasi Jadwal Penerbangan Berbasis Mobile - Sinaga, Ucok; Sabur, Fatmawati (Politeknik Penerbangan Makassar, 2019)
The research aims to design the development of schedule information systems Flights that provide real time information based on the presence of an in-flight aircraft to the user, and generate an information system of flight schedules that are in fact that can provide time information of the aircraft appropriately. Designing the development of flight schedule information system is using UML (Univ (data flow diagram) and designing its application is using mobile technology with the utilization of webservices/API to access flight schedule and Weather information. The departure schedule is a JSON file obtained from the FIDS website of Makassar Hasanuddin Airport, while the weather information of the original airport and the airport passenger's destination is obtained from the Open Wheater API.